Developing an Ethnomathematics-Based Transformational Geometry Textbook to Enhance Students' Mathematical Literacy - Sam, Fitrayuddin; Alam, Syamsu; Patmaniar, Patmaniar (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
An ethnomathematical approach that integrates Luwu culture, especially the Rongkong batik motif, is expected to bridge abstract mathematical concepts with students’ daily lives through the use of local wisdom as a learning context. This study aims to develop ethnomathematics-based transformational geometry textbooks that are feasible, practical, and effective in improving senior high school students’ mathematical literacy. The research employed the ADDIE development model. The participants were Grade XI students and mathematics teachers at SMA Negeri 5 Luwu Utara. The instruments used included teacher and student needs analysis questionnaires, expert validation sheets, teacher and student practicality questionnaires, lesson implementation observation sheets, and a mathematical literacy test administered as a pretest and posttest. Validation by material and media experts was conducted to assess the feasibility of the textbook in terms of content, presentation, construction, and readability. The results show that the developed textbooks are classified as very feasible based on content, presentation, construction, and readability validation. The textbooks were also judged to be very practical by both teachers and students. In terms of effectiveness, there was a significant increase in students’ mathematical literacy after using the textbooks, with an average n-gain of 0.81 (high category). Inferential analysis further indicated a significant difference between students’ pretest and posttest scores. Thus, the ethnomathematics-based transformational geometry textbooks developed in this study are feasible for use in classroom instruction and effective in improving high school students’ mathematical literacy. This study recommends local culture-based textbooks as an alternative form of contextual teaching materials with multicultural characteristics.